Virtual or face to face classes: Ecuadorian university studentsâ€™ perceptions during the pandemic - Sevy-Biloon, Julia (English Language Teaching Educational Journal, 2021)
Due to the pandemic, classes have moved online for 2020-2021, and a return to face-to-face classes in the National University of Education (UNAE) in Ecuador is unknown. Students studying in the undergraduate program to be English language teachers are slowly adapting to this new form of E-learning, and some have found that they prefer online classes, while many are waiting for the day they return to classes. The objective of this study is to look at the pros and cons given by 69 students discussing why taking classes virtually or face to face is a better option for EFL and being an ELT professional in these turbulent times.Â  Some prefer online learning for various reasons such as safety, comfort, economic reasons, and having more time in general. While some find E-learning difficult and want to return to synchronous classes because they feel there is little interaction between classmates and teachers, cannot practice English authentically, cannot get clarification from the teacher, have a hard time concentrating online, and there are constant internet connection issues. In conclusion, this information has great importance for teachers today who are struggling to teach in this new medium and teach to the needs of their students to aid in their planning and will contribute to future teachers who will teach online.Â